Behavioural and neurodevelopmental outcome of 2-year-old children after preterm premature rupture of membranes: follow-up of a randomised clinical trial comparing induction of labour and expectant management. (November 2015) - van der Heyden, Jantien L.; Willekes, Christine; van Baar, Anneloes L.; van Wassenaer-Leemhuis, Aleid G.; Pajkrt, Eva; Oudijk, Martijn A.; Porath, Martina M.; Duvekot, Hans (J) J.; Bloemenkamp, Kitty W.M.; Groenewout, Mariette; Woiski, Mallory; Nij Bijvank, Bas; et al.
Abstract: Objective: We recently reported that induction of labour does not improve short term neonatal outcome in women with late preterm premature rupture of membranes (PPROM) as compared to expectant management (PPROMEXIL trial). In this study the neurodevelopmental and behavioural outcome of the children from this trial at 2 years of age was studied. Study design: We studied outcome of offspring of women randomised in the PPROMEXIL study. These women had >24 h of ruptured membranes and were between 34 and 37 weeks of pregnancy when they were randomised to induction of labour (IoL) or expectant management (EM). Two years after delivery, the parents received the ages and stages questionnaire (ASQ), the child behaviour checklist (CBCL) and a general questionnaire. Results: Follow-up data were obtained from 234 children (121 after IoL, 113 after EM, response rate 59% (44% of the original 532 randomised women)). In the IoL group 16 children (14%) had an abnormal score in ≥1 domains of the ASQ, versus 27 (26%) in the EM group (difference in percentage −11.4 (95% CI −21.9 to −0.98; p = 0.033)). For the CBCL, an abnormal score was found in 13% ( n = 15) in the IoL group and in 15% ( n = 16) in the EM group (difference in percentage −2.13 (95% CI −11.2 to 6.94; p = 0.645)). Conclusion: Although a policy of induction of labour in women with late PPROM does not improve short term neonatal outcome, it might be associated with a decrease in neurodevelopmental difficulties at the age of two years as compared to expectant management. Expectant management did not lead to a difference in behavioural problems.